Development of Interactive Learning Media Based on Learning Management System in Class X English Learning at SMAN 1 Gunungputri - Nurkamilah, Siti; Hartono, Rudi (CV. Media Inti Teknologi, 2024)
This research aims to develop, test the feasibility, and measure the effectiveness of developing interactive learning media based on the Learning Management System in class X English subjects at SMAN 1 Gunungputri. This research uses the ADDIE development model. To test feasibility, researchers used validation from media experts, learning design experts and material experts and considered the results of user responses, namely teachers and students. The feasibility test results obtained from media experts were 74%, instructional design experts were 85%, material expert tests were 98%, teacher users were 92%, small group tests were 95% and large group tests were 97%. These results indicate that the use of interactive learning media is suitable to support the process of English learning activities in class X at SMAN 1 Gunungputri. Data analysis of pre-test and post-test scores showed that the average pre-test score of students was 55 and the average post-test score was 89. The results of effectiveness testing using the N-Gain test showed a result of 0.8, which is at “Effective” category. So, it is concluded that the use of interactive media based on the Learning Management System is effective in improving the learning outcomes of class X students at SMAN 1 Gunungputri.